Iron EDTA ingestion and toxicosis in 61 dogs: a multicenter retrospective study of Australian hospital records - Luswanto, Elvany; Sharp, Claire R.; Mooney, Erin; Purcell, Sarah L. (Frontiers in Veterinary Science, 2025)
IntroductionThere is limited published information on iron toxicosis in dogs, and it is unclear if dogs follow the four stages of progression as in humans. The objective of this retrospective case series was to describe the clinical course and treatment of dogs presenting after iron EDTA ingestion.MethodsCases were retrieved through an electronic medical records search at three veterinary teaching hospitals and three private referral hospitals in Australia. Non-parametric descriptive statistics are reported.Results61 dogs met the inclusion criteria. The most common iron-containing product ingested was iron EDTA molluscicide (60/61), with only one dog ingesting iron EDTA plant fertilizer. Notably, 20 out of 61 dogs (32.8%) had no clinical signs before presentation. Vomiting without blood was the most common clinical sign (21), followed by lethargy (16), diarrhea without blood (15), ataxia/weakness (12), and signs consistent with abdominal pain (10). Abdominal pain was the most common physical examination finding (21), followed by dehydration (10). Forty dogs underwent some form of gastrointestinal decontamination. The median pre-chelation serum iron concentration was 61.3 μmol/L (Min–Max 9–356, n = 40), while the median post-chelation concentration was 14.7 μmol/L (5.72–44, n = 22). Overall, 10 dogs were managed as outpatients, while 51 dogs were treated as inpatients. Inpatient treatments included desferoxamine (43), gastroprotectants (41), antiemetics and/or prokinetics (36), analgesia (24), and hepatoprotectants (4). The most common protocol for desferoxamine administration was a continuous intravenous infusion at 15 mg/kg/h (n = 27); other dogs received 40 mg/kg intramuscularly (n = 13). Two dogs had an anaphylactic reaction to an inadvertent bolus of desferoxamine, while two had allergic reactions possibly related to desferoxamine. Two dogs developed neutropenia, and one developed acute respiratory distress syndrome, possibly as a result of desferoxamine treatment. Overall, 91.8% of dogs survived to discharge. One dog died during hospitalization, experiencing cardiac arrhythmias, shock, and cardiac arrest despite treatment. When considering the stage of iron toxicoses, 16/61 (26.2%) dogs never developed clinical toxicosis, 44 dogs (72.1%) had evidence of Stage 1 clinical signs, 4 dogs (6.6%) also had evidence of Stage 2 clinical signs, and 19 dogs (31.1%) progressed to Stage 3 clinical signs. No dogs had Stage 4 clinical signs (delayed gastrointestinal stricture). A single case was euthanized for acute hepatic failure upon re-presentation after initial survival to discharge.ConclusionIron EDTA toxicosis has a good prognosis in dogs following prompt treatment, but severe organ damage, including hepatic and cardiovascular dysfunction, can occur. Additionally, desferoxamine was well tolerated when administered according to published protocols, but potentially fatal adverse effects can occur.